Nitrogen nutrient status induces sexual differences in responses to cadmium in Populus yunnanensis - Chen, Lianghua (Journal of experimental botany, 2011)
Populus yunnanensis was employed as a model species to detect sexual differences in growth, physiological, biochemical, and ultrastructural responses to cadmium (Cd) stress, nitrogen (N) deposition, and their combination. Compared with the control conditions, Cd decreased plant biomass, damaged the photosynthetic apparatus, visible as a decreased maximum efficiency of photosystem II (PSII; F(v)/F(m)) and effective quantum yield of PSII (Yield), depressed gas exchange capacity, and induced oxidative stress, visible as the disruption of antioxidative enzymes and accumulation of reactive oxygen species (ROS), in both sexes. On the other hand, Cd toxicity was mitigated by the recovery of gas exchange capacity, a decrease in ROS, and improvement of the redox imbalance in both sexes when N deposition was applied. However, males showed a higher gas exchange capacity, lower enzyme inhibition and ROS accumulation, stronger abilities to maintain cellular redox homeostasis, and a better maintenance of chloroplast ultrastructure than did females when exposed to Cd stress alone. Although males exhibited a higher Cd content in leaves than did females, males also accumulated higher levels of non-protein thiols (NP-SHs) and free amino acids (FAAs) for detoxification than did females. Sexual differences induced by Cd, visible, for example, in F(v)/F(m), Yield, net photosynthesis rate (A), and stomatal conductance (g(s)), decreased under N deposition, as no significant differences between the sexes existed in these parameters under the combined treatment. The results indicated that females are more sensitive to Cd stress and suffer more injuries than do males. Moreover, N deposition can mitigate Cd toxicity and decrease sexual differences in Cd sensitivity